Sistem Informasi Database Sertifikat Keterampilan Kerja (SKTK) pada LPJKD Aceh berbasis Web - Aliman Aliman (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2020)
The purpose of this research is to design an application system that is able to record the Work Skills Certificate (SKTK) in LPJK Aceh Province so that it can improve performance in database processing activities at a better level of effectiveness and efficiency. System design used using the waterfall model can support the design of database information Work Skills Certificate (SKTK) in LPJKD Aceh based on the web with additional steps in documenting the software development process, as well as data collection techniques using research methods with observation, interviews, and studies literature. In developing applications that are used in various web programming languages and MySQL is used as a database media. The results of the study succeeded in building a database of Work Skills Certificate (SKTK) and have been implemented to users to get feedback about the prototype developed.